Captura de CO₂ por una comunidad de microalgas obtenidas de un ecosistema natural mexicano - Toledo Cervantes, Alma Lilia (Universidad Autónoma Metropolitana, 2010)
The aim of this research was to characterize the CO₂ capture and growth in a photobioreactor using microalgae cultures. The biological material was obtained from the lake Poza Churince located 19.5 km southwest from Cuatro Ciénegas. Bubble column reactor (BCR) and airlift reactor (ALR) were used throughout the study. The reactors were fed with air streams at 0.8 vvm with 5 and 10% of CO₂ v/v and a light exposition of 3260 Lux. After 19 days, 3.25 Kg m⁻³ and 3.9 Kg m⁻³ of biomass was obtaining for the ALR and BCR, respectively operating at 5% of CO₂. Maximum CO₂ capture rates were 17.13 and 20.8 Kg m⁻³ d⁻¹ for the ALR and BCR, respectively. When feeding at 10% CO₂ stream, the final biomass content was determined to be 3.8 and 2.6 Kg m⁻³ for the BCR and ALR, meanwhile the respective maximum CO₂ capture rates were 21.98 and 26.38 Kg m⁻³ d⁻¹ . In both operation conditions, biofilm attachment was observed on the ALR walls. Conversely the attachment was not detected for the BCR, causing a decrease in biomass concentration and a lower CO₂ capture. Because of the decreased activity in the ALR due to biofilm attachment, it was decided to continue experiments only in the BCR. Additionally, it was observed that the microalgal community composed of Chlorophyta and Cyanobacteria turned into a unialgal culture. It was concluded that the microalga dominant belongs to the division: Chlorophyta, order: Chlorococcales, family Coccomyxaceae, genus: Ourococcus Grobety. It was concluded that increasing the light intensity of 8000 Lx cause an increment in the kinetic parameters of Ourococcus sp. (Xmax, maximum biomass; μmax, specific maximum growth rate; Pmax, maximum productivity; PCO₂, CO₂ fixation rate). Maximum biomass was obtained at 8000 Lx and 5% CO₂ (6 Kg m⁻³ ). However a reduction in the removal rates (% RCO₂) and the elimination capacity in the system (EC) was observed at this operation condition. High CO₂ feeding rates promote higher carbon captures. Nevertheless enhancement in Pmax was not obtained at high CO₂ feeding rate. Additionally, a flow at 0.8 vvm increased productivity and biomass concentration. The maximum CO2 fixation rate, removal rate and elimination capacity was attained at 10% CO₂, 5620 Lx and flow at 0.8 vvm. No inhibition was observed operating a gas streams with 10% CO₂ and loading rate up to 160 Kg CO₂ m⁻³ d⁻¹ . The maximum %RCO₂ was 25% supplying 10% CO₂ at 0.4 vvm and 5620 Lx. The PCO₂ and Pmax using microalgae are lower than those obtained in this study. For example, de Morais and Costa (2007c) observed that Chlorella kessleri Fott et Nováková shows a PCO₂ of 0.163 Kg m⁻³ d⁻¹ and Pmax of 0.087 Kg m⁻³ d⁻¹ , also in 2007a with Spirulina sp. same authors obtained a PCO₂ of 0.413 Kg m⁻³ d⁻¹ and a Pmax of 0.22 Kg m⁻³ d⁻¹ . In this study using Ourococcus sp. a PCO₂ of 0.92 Kg m⁻³ d⁻¹ and a Pmax of 0.517 Kg m⁻³ d⁻¹ was obtained. On the other hand, Ourococcus sp. shows the ability to store up to a 20-30% of its dry weight as oil. Therefore these algae can be used as raw material to obtain oil, since a productivity of 0.5 Kg m⁻³ d⁻¹ with a maximum biomass of 6 Kg m⁻³ was obtained.; El objetivo de esta investigación fue caracterizar la captura de CO₂ y el crecimiento en un fotobiorreactor de una comunidad de algas obtenidas de la laguna de Churince, localizada a 19.5 Km al sur-oeste de Cuatro Ciénegas, Coahuila. Al inicio de los experimentos se estudiaron dos configuraciones de reactores: columna de burbujas (BCR) y airlift (ALR). Las condiciones iniciales fueron: flujo de alimentación de 0.8 vvm con concentración de CO₂ al 5 y 10% CO₂ v/v y una intensidad de luz de 3260 Lx. En el experimento al 5% se obtuvo en el ALR una biomasa de 3.25 Kg m⁻³ y en el BCR de 3.9 Kg m⁻³ , bajo estas condiciones la máxima captura de CO₂ fue de: 20.8 y 17.13 Kgm⁻³ d⁻¹ para el BCR y ALR, respectivamente. Cuando se alimentó la corriente gaseosa con CO₂ al 10%, la biomasa final obtenida fue 3.8 Kg m⁻³ para el BCR y 2.55 Kg m⁻³ para el ALR, así mismo las capturas de CO₂ máximas fueron de 21.98 y 26.38 Kg m⁻³ d -1 para el BCR y ALR, respectivamente. En ambos casos se observó la formación biopelículas dentro de las paredes del ALR, lo que ocasionó una disminución en la biomasa suspendida y, en la captura de CO₂. Debido a la disminución de la actividad en el ALR se continuó con los experimentos solo en el BCR. Durante la operación de los fotobiorreactores se observó que, la comunidad compuesta por microalgas de las divisiones Chlorophyta y Cyanobacteria se transformó en un cultivo prácticamente unialgal. La microalga predominante pertenece a la división: Chlorophyta, orden: Chlorococcales, familia: Coccomyxaceae, género: Ourococcus Grobety. Se concluyó que incrementar la intensidad de luz a 8000 Lx permite aumentar los parámetros cinéticos de Ourococcus sp. (biomasa máxima Xmax, tasa de máxima de crecimiento específico µmax, productividad máxima Pmax, tasa de fijación de CO₂ PCO₂). La biomasa máxima registrada se obtuvo a 8000 Lx y 5% de CO₂ (6 Kg m⁻³ ), sin embargo también se observó una disminución en los porcentajes de remoción (%RCO₂) y la capacidad de captura de CO₂ en el sistema (CE). La CE se incrementó al suministrar una mayor carga, sin embargo no se observó un incremento en la Pmax. Por otro lado, se observó que incrementar el flujo de entrada a 0.8 vvm indujo mayor productividad y concentración de biomasa. Además la mayor PCO₂, %RCO₂ y la máxima CE se logró a 10% CO₂, 5620 Lx y flujo de 0.8 vvm. En estos experimentos no se observó inhibición por la cantidad de CO₂ suministrado, Ourococcus sp. crece con corrientes gaseosas enriquecidas con 10% y con cargas de CO₂ de hasta 160 Kg m⁻³ d⁻¹ . El máximo %RCO₂ obtenido fue 25% con suministro de 10% CO₂ v/v a 0.4 vvm. Las PCO₂ con respecto a la biomasa y la Pmax medida en algunas especies de microalgas utilizadas en la remoción de CO₂ de corrientes gaseosas son menores a las obtenidas en este estudio, por ejemplo de Morais y Costa (2007c) obtuvieron con Chlorella kessleri Fott et Nováková, una PCO₂ de 0.163 Kg m⁻³ d -1 y Pmax de 0.087 Kg m⁻³ d⁻¹ , además en 2007a, con Spirulina sp. obtuvieron una PCO₂ de 0.413 Kg m⁻³ d -1 y Pmax de 0.22 Kg m⁻³ d⁻¹ , mientras que con Ourococcus sp. se obtienen PCO₂ de 0.92 Kg m⁻³ d -1 y Pmax de 0.517 Kg m⁻³ d⁻¹ . Por otro lado, Ourococcus sp. contiene 20-30 % de aceites con respecto a su peso seco, por lo tanto se cree que puede tener potencial biotecnológico para la obtención de aceites.